Study of 2D and 3D Optical Beam Induced Voltage Imaging Using Photoresistor Sensor - Warsito, Warsito; Suciyati, Sri Wahyu; Harnani, Susi; Dzakwan, Akhmad (UI Scholars Hub, 2005)
Study of 2D and 3D Optical Beam Induced Voltage Imaging Using Photoresistor Sensor. This article shows a method to study OBIV (optical beam induced voltage) imagerie system, that usually employ a laser scanning microscopy system. The OBIV imagerie system developed use a photoresistor sensor as a sample and simultaneously it can be used for analyzing its inhomogeneity response. Resolution of the system is still low, about 350μm due to high value of incident light diameter. The results inform that photoresistor sensors gave an optimum response if the incident light hits the center of sensible zone.